First Indian at the South Pole - Sehra, Parmjit Singh (SCHOOL SCIENCE, 2013)
Adaptability certificate: Thinking that the Russian doctor on board the ship ‘Viese’ sailing to Antarctica might be asking for my International Health Certificate, I promptly gave him that. But he smiled and remarked, “Wintering over the South Polar Ice-cap where the temperatures range from -40 to -90°C and the winds blow with speeds exceeding 200-300 km per hour is not a joke, my friend. Your certificate is meant only for the posh cities of the world. Antarctica demands from an individual the utmost in physical stamina and mental soundness with mature judgement so that a man working there may act quickly and positively in order to survive. Prior to selection for Antarctica, we conduct a thorough medical check-up and a tough physiological and psychological screening of our expedition members and also impart them a special training. Only after qualifying all these tests and training they are given ’adaptability certificate’ and taken to harshest continent Antarctica”.